2011
DOI: 10.2304/plat.2011.10.1.3
|View full text |Cite
|
Sign up to set email alerts
|

Misconceptions and Conceptual Change in Undergraduate Students' Understanding of Psychology as a Science

Abstract: American undergraduate psychology students' (N = 438) beliefs about the scientific nature of the discipline were assessed as a function of their year in college (first to fourth year) and academic status in psychology (a comprehensive, limited, or minimal program of study in psychology). Students completed the Psychology as a Science (PAS) questionnaire, in which they evaluated 15 Likert-type statements about scientific psychology. There was a main effect of year in college and academic status, suggesting that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
29
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(35 citation statements)
references
References 25 publications
3
29
0
Order By: Relevance
“…While certainly influenced by the wider social context, it may be the case that this misconception (among others) is rooted in an underlying naïve ontology that differs dramatically from contemporary theory and research. In other words, several misconceptions may represent the outcome of a collection of ontological assumptions, explanatory concepts and causal mechanisms that, when taken together, form the basis of intuitive theories about psychology (Amsel, Baird, & Ashley, 2011). For instance, the common belief in mind-body dualism (Bloom, 2004) may propagate a variety of misconceptions surrounding extrasensory perception, memories of previous lives and 'out-of-body experiences' (Lilienfeld et al, 2009).…”
Section: What Are Psychological Misconceptions?mentioning
confidence: 99%
See 1 more Smart Citation
“…While certainly influenced by the wider social context, it may be the case that this misconception (among others) is rooted in an underlying naïve ontology that differs dramatically from contemporary theory and research. In other words, several misconceptions may represent the outcome of a collection of ontological assumptions, explanatory concepts and causal mechanisms that, when taken together, form the basis of intuitive theories about psychology (Amsel, Baird, & Ashley, 2011). For instance, the common belief in mind-body dualism (Bloom, 2004) may propagate a variety of misconceptions surrounding extrasensory perception, memories of previous lives and 'out-of-body experiences' (Lilienfeld et al, 2009).…”
Section: What Are Psychological Misconceptions?mentioning
confidence: 99%
“…Still others argue that misconceptions do not reflect inaccurate or incomplete prior beliefs, but rather a core set of explanatory concepts that people use to understand, predict and influence behaviour (termed 'folk psychology'; Amsel et al, 2011). It is worth noting, however, that these environmental and cognitive factors have generally been supported more by argument than empirical evidence (Chew, 2006).…”
Section: Prevalence and Origins Of Psychological Misconceptionsmentioning
confidence: 99%
“…For instance, Pettijohn et al (2011) found a significant increase in PAS scores for students who had completed either a research methods course or a psychology thesis. Similarly, others have found that fourth year psychology majors that had completed more advanced psychology courses displayed higher PAS scores compared to first year undergraduate students (Amsel et al, 2011;Pettijohn et al, 2015).…”
Section: Sizemore and Lewandowskimentioning
confidence: 87%
“…A variety of explicit measures has been employed to assess people's conceptions of science and psychology. To more directly assess whether students believe that psychology is a science, the most frequently administered explicit measure has been Friedrich's (1996) Psychology as a Science Scale (PAS) (Amsel et al, 2011;Bartels, Hinds, Glass, & Ryan, 2009;Holmes & Beins, 2009;Pettijohn et al, 2015;Provost et al, 2011). People's psychological interests may be related to the manner that they view the discipline.…”
Section: Explicit Attitudes Of Psychologymentioning
confidence: 99%
See 1 more Smart Citation